Influence of Corrosion Damages on Carrying Ability of Oil Pipelines - A.N. Kozik; V.V. Vorobyov (Механика машин, механизмов и материалов, 2011)
Characteristic kinds of local corrosion damage of an internal surface of pipes of underwater transitions after long (more than 35—40 years) operation are established: in the form of an oval and an extended strip; the mechanism of their formation is described. By specially put natural experiments (destruction of petrowire pipes at test under pressure) is shown that after long operation zones with local corrosion damages are dangerous not zones of longitudinal welded connections, namely. The method and technology of restoration of working capacity of underwater transitions after their long operation is stated; it provides decrease in risk of failures and safety increase.